Phylogenetic implications and characterization of the chloroplast genome of Atractylodes macrocephala (Compositae), an herb species to China. Issue 1 (2nd January 2023) - Zhu, Bin; Cao, Tianyi; Lang, Yuying; Fei, Jun
Abstract: The rhizome of Atractylodes macrocephala is one of the most commonly used herbs in China. In this paper, we presented the complete chloroplast genome of A. macrocephala . The chloroplast genome of A. macrocephala is 153, 256 bp in length as the circular, which harbors a large single-copy (LSC) region 84, 291 bp, a small single-copy (SSC) region of 18, 675 bp and separated by a pair of inverted-repeat (IR) regions of 25, 145 bp for each one. The overall nucleotide content of the chloroplast genome is 37.7% GC content. This chloroplast genome contains 125 genes, which includes 88 protein-coding genes (PCGs), 29 transfer RNA (tRNAs) and 8 ribosome RNA (rRNAs). Phylogenetic implications based on chloroplast genomes of 16 the family Compositae plant species indicated that Atractylodes macrocephala was closely related to Atractylodes lancea in the family Compositae by the Maximum-Likelihood (ML) method.